Gain(1)(q21) is an unfavorable genetic prognostic factor for patients with relapsed multiple myeloma treated with thalidomide but not for those treated with bortezomib - Smetana, Jan; Berankova, Kristina; Zaoralova, Romana; Nemec, Pavel; Greslikova, Henrieta; Kupska, Renata; Mikulasova, Aneta; Frohlich, Jan; Sevcikova, Sabina; Zahradova, Lucie; Krejci, Marta; Sandecka, Viera; et al. (Clinical lymphoma, myeloma & leukemia, 2013)
UNLABELLED: Chromosomal aberrations are important prognostic factors in multiple myeloma diagnosis. We evaluated the effect common high-risk chromosomal aberrations in a cohort of 102 patients with relapsed disease treated with bortezomib or thalidomide. Our results showed that patients treated with thalidomide with a gain(1)(q21) had inferior survival compared with the bortezomib group. Therefore, bortezomib-based regiments are more effective for patients with relapsed multiple myeloma with an incidence of gain in the gain(1)(q21). BACKGROUND: Prognostic impact of specific chromosomal aberrations in patients with relapsed multiple myeloma (MM) treated with the novel agents is briefly described. PATIENTS AND METHODS: We analyzed the prognostic value of an extended panel of chromosomal aberrations [del(13)(q14), del(17)(p13), t(4;14)(p16;q32), gain(1)(q21), and hyperdiploidy] by using the technique of interphase fluorescence in situ hybridization in a cohort of 102 patients with relapsed MM treated with thalidomide- or bortezomib-based protocols. RESULTS: The gain(1)(q21) had a negative impact on overall survival for patients with MM treated with thalidomide (15.7 vs. 41.3 months; P = .004). Moreover, we confirmed the negative impact of the cumulative effect of 2 or more cytogenetic changes that occur simultaneously on the overall survival in the thalidomide group (20.3 months vs. not yet reached; P = .039). We did not find any significant impact of the aberrations studied on overall survival in the bortezomib cohort of patients. CONCLUSION: We conclude that bortezomib-based protocols are able to partially overcome the negative prognostic impact of the tested chromosomal abnormalities in patients with relapsed MM.
Keywords: pyraziny; Trisomy; dospělí; Prognosis; senioři nad 80 let; trizomie; Humans; staging nádorů; lidé středního věku; Neoplasm Staging; Recurrence; Antineoplastic Agents; Aged, 80 and over; Middle Aged; Bortezomib; protinádorové látky; Multiple Myeloma; prognóza; Boronic Acids; incidence; kyseliny boronové; mužské pohlaví; bortezomib; Adult; Chromosome Aberrations; Chromosomes, Human, Pair 1; výsledek terapie; recidiva; Treatment Outcome; ženské pohlaví; Thalidomide; lidské chromozomy, pár 1; lidé; Incidence; Aged; Pyrazines; senioři; mnohočetný myelom; Male; thalidomid; chromozomální aberace; Female